2006
DOI: 10.1002/pits.20204
|View full text |Cite
|
Sign up to set email alerts
|

Implementing school‐wide behavior change: Lessons from the field

Abstract: In this article, we examine two schools that successfully adopted school-wide positive behavior interventions and highlight some of the common features that contributed to their success. As part of our analysis, we draw upon the theoretical literature on organizational change to discuss factors that supported these successful school-wide reform efforts, including the contributions of administrators, teachers, and school psychologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
(14 reference statements)
0
27
0
2
Order By: Relevance
“…George, White, and Schlaffer (2007) have stated that there has been a great deal of change attempts regarding the education which are planned comprehensively in the last twenty-five years; however most of these attempts have succeeded in a rather limited proportion. With regards to this, Awbrey (2005) has stated that the most important obstacle for organizational change, generally containing the educational innovation attempts is that the significant effect of organizational culture is not taken into account in the process of change and he has also asserted that in order to provide a successful and continuous change, it is required that the cultural and structural approaches towards change are integrated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…George, White, and Schlaffer (2007) have stated that there has been a great deal of change attempts regarding the education which are planned comprehensively in the last twenty-five years; however most of these attempts have succeeded in a rather limited proportion. With regards to this, Awbrey (2005) has stated that the most important obstacle for organizational change, generally containing the educational innovation attempts is that the significant effect of organizational culture is not taken into account in the process of change and he has also asserted that in order to provide a successful and continuous change, it is required that the cultural and structural approaches towards change are integrated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary interventions are for those who demonstrate risk factors and who require more specialized forms of behavioural support . They provide additional skill instruction and can be implemented, for example, in the form of tutoring and mentoring programs (George, White & Schlaffer, 2007) . They approximately target 5-10% of student population.…”
Section: "Appropriate Behavior" or Population Management Through Pbismentioning
confidence: 99%
“…Taken together, results from these two studies suggest that: (a) reasons for initiating reforms (i.e., Phase I) may be varied; (b) decisions to initiate educational reform efforts are more likely to emerge from administrators rather than from teachers; and (c) shared decision-making and vision between teachers and administrators, at Phase I, is typically not sought or achieved. Unfortunately, as prior research has suggested (George et al, 2007;Kincaid et al, 2007), lack of a shared vision among educators can inhibit or entirely thwart implementation of educational reform efforts.…”
Section: Phase Imentioning
confidence: 99%
“…District support was the most important facilitator, followed by factors such as SWPBS project support, effective use of data, administrative support, school-level/team trainings, plan implementation, and team membership. Together with the findings from George, White, and Schlaffer (2007), this research suggests that educational change can be successful when conditions that build the capacity of both organizations and individuals are created and the culture of classrooms and schools are changed (D. Kincaid, personal communication, June 21, 2007).…”
Section: Rti As An Educational Change Initiativementioning
confidence: 99%
See 1 more Smart Citation